USING NEFOPAM FOR MANAGEMENT OF POSTOPERATIVE SHIVERING. - Dr. Ayad Najm Abdulameer; Dr. Noor Alimardan Mohamad; Dr. Layth Masood Saleh (Scholar Express Journals, 2022)
This paper aims to using nefopam for the management of postoperative shivering, and in this study, 60 patients were collected and distributed into two groups (the first group was nefopam for 40 patients) (and the second group was meperidine for 20 patients) Sixty patients were included, and the average age was (30-60 years), and 10.88±1.11 mg of nefopam was given to 40 patients; as for the comparison group, 11.1±0.98 of meperidine was given. The response rate in this study was for the nefopam group for 38 patients with (95%) In the comparison group; it was somewhat lower for 17 patients with (85%); the duration of shivering after surgery was reduced in the group of patients for nefopam 4.11 ± 1.2, while for the control group, the duration of shivering after surgery was reduced by 3.11 ± 0.56 The use of nefopam allows the cessation of shivering after surgery in 95% of patients. A single bolus dose of nefopam is sufficient for the rapid cessation of muscle tremors. No recurrent episodes of muscle twitching, nausea, vomiting, sweating, or tachycardia were observed. The main cause of intraoperative or postoperative tremor is intraoperative hypothermia, which is caused by a violation of thermoregulation against the background of the action of anaesthesia. The development of hypothermia in the period of surgery is primarily associated with a defect in the physiological mechanisms of thermoregulation, which are affected by general and local anaesthesia.
Keywords: Nefopam; Anaesthesia; Vomiting; ASA